(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The article deals with a comparative analysis of the semantic characteristics of paremiological units (PU) with a modality element, explaining an animalistic feature in Spanish, English, and Tatar languages. PU with that factor is of tremendous interest for examining the linguistic world-view of the Spanish, English, as well as Tatar languages. The significance of this study lies in the fact that phraseological units are complicated and controversial notions in linguistics. A descriptive-analytical method is utilized to meet the study’s aims. This research topic is substantial to modern linguistic sciences so as to detect the characteristics and structure of the PU of the Tatar languages, Spanish, and English. This paper examines the animalistic character of the paremiological units with the modality element in the various comparative languages. The common and specific types utilizing the modality element in linguistics and also in their classification are taken into consideration. The study’s results obtained are of utmost importance for scientists who study the phraseological units’ concepts in Tatar languages, Spanish, as well as English. These outcomes can be applied to the inspection and the examination of research and cultural problems and also to the procedures of language learning.